Adolescent and Parent Experience of Care at a Family-Based Treatment Service for Eating Disorders - Hughes, Elizabeth K.; Poker, Suzannah; Bortz, Amy; Yeo, Michele; Telfer, Michelle; Sawyer, Susan M. (Frontiers in Psychiatry, 2020)
Objective: Incorporating consumer perspectives is an important but often overlooked opportunity to optimize treatment engagement and outcomes for adolescents with eating disorders. This study explored the experience of care of adolescents and their parents at a multidisciplinary specialist eating disorders service providing family-based treatment (FBT) as first-line treatment. Method: Eighty-five adolescents and 145 parents who completed FBT at the service between 2013 and 2015 were surveyed about their experience of service access, intake assessment, education, support, interactions with the treatment team, recovery, and the discharge process. Results: Overall families were very positive about their experience, particularly in regard to assessment, education, interactions with the team, and achieving physical health. Although parents tended to be more satisfied, adolescents also held the service in high regard. Some areas were identified that could be improved, including treatment delays, carer support, therapeutic alliance, and preparation for discharge. Conclusions: These results indicate a need for greater focus from specialist eating disorder services to ensure that the services provided, including FBT, fully meet the needs of families and optimize adolescents’ treatment experiences.